Phylogenetics of Escallonia (Escalloniaceae) based on plastid DNA sequence data - Sede, Silvana Mabel (2013)
Escallonia (Escalloniaceae) is a New World genus of c. 39 species distributed mainly in the South American highlands. Plastid DNA sequence data from the intergenic spacers trnS-trnG and 3′ trnV-ndhC and the ndhF gene for 32 species were used to examine the relationships among species and related genera and to analyse the relationship between phylogeny and the geographical distribution of the species. Maximum parsimony and Bayesian inference were employed to analyse the data. The sister relationship of Escallonia to Forgesia and Valdivia was corroborated. We recovered five strongly supported clades that are geographically structured, suggesting that the evolutionary history of the genus may be linked to historical processes, including the uplift of mountainous systems in South America.